APPLYING SMALL GROUP DISCUSSION TO ENHANCE STUDENTS’ SPEAKING ABILITY AT SMA N 1 POIGAR - Tini Mogea; Elisabeth Zuska Oroh (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this research is to find out the effectiveness of small group discussion technique in improving the students’s speaking ability. It will be conduct at SMA Negeri 1 Poigar in one class of the first-year students of the school as the sample. The data were collected using test in the form of pre-test and post-test. Teaching speaking skill by using small group discussion technique can improve the students’ ability in speaking. Small group discussion technique can give the students opportunity to practice their language. In small group discussion, they can express their ideas and thought freely. It will be better for English teacher to vary the techniques of teaching to avoid boredom that might appear to the students.